Karakteristik Ibu Bersalin dengan Ketuban Pecah Dini (KPD) di Puskesmas Manisrenggo Klaten - Dwi Indah Wulandari; Fara Khanza Azizah; Catur Setyorini; Fajar Rana Rosyadah (Journal of Applied Agriculture, Health, and Technology, 2024)
Premature rupture of membranes (PROM) is usually defined as the amniotic sac before uterine contractions occur. In 2018, the incidence of PROM is recorded at around 5% to 10% of all labor cases. This study aimed to determine the characteristics of mothers giving birth with premature rupture of membranes (PROM) at the Manisrenggo Klaten Health Center in 2024. The research method was quantitative descriptive. The study population was all mothers who gave birth with PROM at the Manisrenggo Klaten Health Center. This study used secondary data from the KIA data. The sample in this study used a total sampling technique, namely 25 respondents. Univariate analysis is presented in frequency distribution and percentage. The results of the study showed that the incidence of premature rupture of membranes mostly occurred in mothers aged 20-35 years as many as 18 respondents (72%), multiparous as many as 14 respondents (56%), and premature rupture of membranes occurred at term gestational age (100%).